COVID-19 and Interculturality: revisiting assumptions about intercultural competence and criticality development in Modern Language degree programmes. (2nd January 2023) - Parks, Elinor
ABSTRACT: The initial response to Covid-19 exposed widespread racism and Sinophobia across the world, which contributed to a rethinking of equality and diversity in Higher Education (HE) and beyond. Within Modern Languages, much attention has been placed on decolonising the curriculum. The death of George Floyd in 2020 further contributed to an increased awareness of the need to rethink racism and challenge current practice within the curriculum. This paper re-examines the findings of a doctoral study exploring students' development of Intercultural Competence (IC) and criticality in Modern Languages with the aim of revisiting ways in which students' intercultural development can be defined and fostered in Higher Education.